MENO APIBRĖŽTIES PROBLEMA: MORRISO WEITZO METODOLOGINIS REDUKTYVIZMAS. - Straukaitė, Ieva (Problems / Problemos, 2012)
The article analyzes the argument for the impossibility of the definition of art by Morris Weitz which provoked a controversy in contemporary analytic philosophy of art. The typology of its basic components -- the linguistical, the demarcational, the epistemic and the metacritical -- is given. Weitz's reductionist argumentation is asserted to be insufficient for denying the possibility of the definition of art. With the aim of defending "traditional" essentialism, this thesis is grounded by displaying the basic principles of Clive Bell's and Benedetto Croce's conceptions of art. Weitz's method of "similarity conditions" is shown to be based on too broad criteria and thus to fail to solve the problem of the demarcation between art and non-art.